Simultaneous ultrafast determination of six alkaloids in mainstream cigarette smoke by DART-MS/MS. Issue 39 (26th September 2018) - Li, Chao; Li, E'xian; Wu, Yiqin; You, Junheng; Liu, Wei; Cui, Zhuwen; Li, Lijun; Liu, Zhihua; QIN, Yunhua
Abstract : To determine nicotine, nornicotine, myosmine, anatabine, anabasine and nicotyrine in mainstream cigarette smoke simultaneously, a novel method based on Direct Analysis in Real Time (DART) Ionization technique combined with mass spectrometry was established by optimizing parameters such as injection rate, type of extraction solvent and extraction solvent dosage. Abstract : To determine nicotine, nornicotine, myosmine, anatabine, anabasine and nicotyrine in mainstream cigarette smoke simultaneously, a novel method based on Direct Analysis in Real Time (DART) Ionization technique combined with mass spectrometry was established by optimizing parameters such as injection rate, type of extraction solvent and extraction solvent dosage. Ten types of flue-cured tobacco samples were analyzed by the established method, and the results were compared with those obtained using a GC/MS method: (1) under optimized conditions (30 mL ultrapure water as the extraction solvent and with extraction rate of 0.6 mm s −1 ), the analysis could be completed within 20 s. (2) The linear range of the method was 0.002–1000 μg mL −1 with R 2 ≥ 0.9957, the recovery ranged from 80.0% to 122.5%, and the limit of detection and the limit of quantitation were 0.28–5.77 ng mL −1 and 0.92–19.23 ng mL −1, respectively. (3) The relative error between DART-MS/MS and GC/MS methods was 0.24–9.62%. The established method is green, rapid, reliable and suitable for the determination of 6 alkaloids in mainstream cigarette smoke.